Anti-sintering copper oxide / cerium dioxide catalyst and preparation method thereof

By confining copper oxide particles in the layered ceria nanogap layer, the problem of poor thermal stability of copper oxide/ceria catalysts is solved, and a catalyst with high activity and high thermal stability is achieved, which is suitable for catalytic combustion reactions.

CN119500161APending Publication Date: 2025-02-25ZHEJIANG OCEAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411612541.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing copper oxide/ceria catalysts have poor thermal stability, which leads to their sintering easily under high temperature conditions, reducing catalytic activity and service life.

Method used

By using layered ceria nanosheets as support, the copper oxide particles are constrained in the ceria nanogap layer, and the spatial constraint effect of the layered structure is used to limit the sintering of copper oxide and ceria at high temperatures.

Benefits of technology

It improves the thermal stability and catalytic activity of the catalyst, extends the service life of the catalyst, and reduces the preparation cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500161A_ABST
    Figure CN119500161A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-sintering copper oxide / cerium dioxide catalyst and a preparation method thereof, soluble cerium salt is directly impregnated on metal copper salt or copper oxide based on an impregnation method, and the high-activity and anti-sintering copper oxide / cerium dioxide catalyst is obtained through drying and roasting activation. In the preparation process, a unique layered cerium dioxide nanosheet structure is formed, and copper oxide particles are constrained in a layered cerium dioxide nano gap layer through a layered spatial constraint effect; in addition, due to the interaction between the layered cerium dioxide nanosheets and the copper oxide particles and the space intervals between the layered cerium dioxide nanosheets and the copper oxide particles, the sintering phenomena of aggregation, growth and the like of the copper oxide particles and the layered cerium dioxide nanosheets at high temperature are limited; compared with a catalyst prepared by an existing impregnation method, the catalyst prepared by the invention has more excellent activity and sintering resistance, is safe and simple to operate, is low in cost and is easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a sintering-resistant copper oxide / cerium dioxide catalyst and a preparation method thereof. Background Art

[0002] With the development of industry, more and more chemical reactions require the use of catalysts to improve the reaction rate and stability. At present, metal oxide catalysts have been widely used in various catalytic reactions. Copper oxide / ceria catalysts are widely used in the catalytic field due to their unique electrical, magnetic and catalytic properties, as well as excellent redox performance, high oxygen storage capacity and oxygen mobility, such as: CO preferential oxidation, CO catalytic reduction of NO, water gas shift (WGS), selective catalytic reduction (SCR), photocatalytic degradation, photocatalytic hydrogen production, hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and catalytic combustion of VOCs. Among them, copper oxide / ceria catalysts have high catalytic activity in the catalytic combustion reaction of VOCs.

[0003] For example, in reference 1 (Yuchuan Ye. Jing Xu. et a1, CuO / CeO2 catalysts prepared by modified impregnation method for ethyl acetate oxidation, Chemical Engineering Journal, 2023, 471, 144667, Doi: 10.1016 / j.cej.2023.144667), copper nitrate is impregnated in cerium nitrate to prepare cerium dioxide, which is dried, calcined and activated to obtain a copper oxide / cerium dioxide catalyst with high activity and high thermal stability for catalytic oxidation of ethyl acetate. However, due to the low Tammann temperature of copper oxide, the thermal stability of the copper oxide / cerium dioxide catalyst is poor.

[0004] The activity of the catalyst and its thermal stability against sintering are the core of the catalytic combustion method. The activity and thermal stability of the catalytic combustion catalyst directly affect the purification effect of VOCs and the cost of use. The catalytic performance and thermal stability of the catalyst are closely related to the preparation method. Therefore, the preparation of copper oxide / cerium dioxide catalysts with high thermal stability is one of the current technical difficulties.

[0005] The impregnation method is one of the most commonly used methods for preparing various supported industrial catalysts because of its simple preparation and easy large-scale production. The common impregnation method is to impregnate the soluble metal precursor solution such as the nitrate of the active component onto the solid oxide support, and then prepare the supported catalyst through drying, roasting or activation.

[0006] A patent application with publication number CN116493016A discloses a rod-shaped cerium dioxide-loaded metal oxide nanocatalyst and its preparation method and application. Cerium dioxide is used as a carrier, copper oxide nanoparticles are loaded as catalytically active components, N-methylpyrrolidone is used as a solvent, ethylene glycol is used as a reducing agent, and sodium polyacrylate is used as a surfactant. A uniform cerium dioxide carrier sol is obtained by stirring at normal temperature and pressure. The metal copper sol is dropped into the cerium dioxide carrier sol, mixed, dried, and calcined to obtain a cerium dioxide-loaded metal oxide nanocatalyst.

[0007] For example, reference 2 (Sun Shuaishuai. Mao Dongsen. et al, Enhanced CO oxidation activity of copper oxide / cerium dioxide catalyst prepared by surfactant-assisted impregnation method, Journal of Rare Earths, 2015, 33 (12), 1268-1274, Doi: 10.1016 / S1002-0721 (14) 60556-1) adopts a surfactant-assisted impregnation method, based on raw materials copper nitrate and cerium dioxide, cetyl trimethyl ammonium bromide (CTAB) is added to the solution for impregnation, and the catalyst is obtained by drying, calcination and activation. Catalysts prepared by ordinary impregnation methods often result in poor dispersion of metal particles and weak metal-support interaction, resulting in low catalyst activity and thermal stability.

[0008] In addition, by using a common impregnation method to load a small particle carrier component with a large particle metal active component, the service life and sintering resistance of the catalyst can be improved to a certain extent. For example, Reference 3 (Gui-Sheng Wu. Dong-Sen Mao. et al., The Role of the Promoters in CuBased Catalysts for Methanol Steam Reforming, Catalysis Letters 2009, 130, 177-184, Doi: 10.1007 / s 10562-009-9847-8) studied the effects of promoters such as zirconium oxide and zinc oxide on copper catalysts in a methanol steam reforming (MSR) reaction at 260°C, and found that zirconium oxide improved the catalytic activity and stability of copper. However, due to the small specific surface area and fewer active sites of the inversion catalyst, it usually has a lower catalytic activity than a normal supported catalyst.

[0009] Although the impregnation method for preparing catalysts has been disclosed in the prior art, preparing a catalytic combustion catalyst having both high activity and sintering resistance by a simple impregnation method is one of the current technical difficulties and research hotspots. Summary of the invention

[0010] The purpose of the present invention is to provide a sintering-resistant copper oxide / cerium dioxide catalyst and a preparation method thereof. The copper oxide / cerium dioxide catalyst is developed by a simple impregnation method, with cerium dioxide as a carrier and copper oxide as an active substance. The copper oxide is constrained in the nano-gaps of cerium dioxide, thereby improving the activity and sintering resistance of the catalyst.

[0011] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0012] The invention discloses a sintering-resistant copper oxide / cerium dioxide catalyst, which uses cerium dioxide as a carrier and copper oxide as an active material, and the copper oxide is constrained in a nano-gap layer of cerium dioxide.

[0013] Copper oxide is confined in the ceria nano-gap layers. Based on the interaction between the layered ceria nanosheets and the copper oxide particles and the spatial spacing between the layered ceria nanosheets and the copper oxide particles, the sintering of the copper oxide particles and the layered ceria nanosheets at high temperatures is restricted, making the copper oxide / ceria catalyst have high thermal stability.

[0014] Preferably, the cerium dioxide is a layered nanosheet structure, and the copper oxide is a particle structure.

[0015] Layered cerium dioxide is used as a carrier, which has a large specific surface area and good structural stability, and has high chemical stability and thermal stability; copper oxide particles are active substances, which have good catalytic activity and can increase the reaction rate; copper oxide particles loaded on layered cerium dioxide can make the catalyst have excellent catalytic activity and high thermal stability.

[0016] The present invention also provides a method for preparing the sintering-resistant copper oxide / cerium dioxide catalyst, comprising:

[0017] S1. Adding a soluble cerium salt to a solvent and stirring until completely dissolved to obtain an impregnation solution;

[0018] S2. impregnating the impregnation solution obtained in step S1 on a metallic copper salt or copper oxide, standing at room temperature to obtain a mixture, and drying the mixture to obtain a precursor;

[0019] S3. The precursor obtained in step S2 is placed in an air atmosphere and calcined at a temperature of 400 to 800° C. for 2 to 8 hours to obtain a sintering-resistant copper oxide / cerium dioxide catalyst.

[0020] During the heat treatment step of the preparation process, the catalyst forms a unique layered ceria nanosheet structure and granular copper oxide. Through the layered spatial confinement effect, the copper oxide nanoparticles are confined in the layered ceria nanogap layers, limiting the aggregation and growth of copper oxide nanoparticles and layered ceria nanosheets at high temperatures. This is why copper oxide / ceria has better activity and high thermal stability.

[0021] Preferably, the soluble cerium salt is one or more of cerium nitrate, cerium chloride, cerium citrate and cerium acetate.

[0022] The present invention uses a soluble cerium salt to provide a cerium source to form cerium dioxide as a carrier for loading active substances.

[0023] Furthermore, the soluble cerium salt is cerium nitrate.

[0024] Preferably, the solvent is one or more of water, methanol, ethanol and propanol.

[0025] Selecting a suitable solvent can dissolve the catalyst precursor and promote the reaction.

[0026] Furthermore, the solvent is deionized water or distilled water.

[0027] Preferably, the mass ratio of the soluble cerium salt to the solvent is 1.30-1.40:1.

[0028] The amount of the solvent is determined according to the solubility of the soluble cerium salt, so that the soluble cerium salt can be just dissolved in the solvent without obvious excess precipitation.

[0029] Furthermore, the mass ratio of the soluble cerium salt to the solvent is 1.304:1.

[0030] Preferably, the metal copper salt is one or more of copper acetate, copper carbonate and copper oxalate.

[0031] The present invention uses one or more of copper acetate, copper carbonate and copper oxalate to provide a copper source with low solubility as an active substance. During the preparation process, the reaction generated by high-temperature roasting can remove other impurities and ions.

[0032] Preferably, the mass ratio of the metallic copper salt or copper oxide to the soluble cerium salt is 0.03-0.1:1.

[0033] Furthermore, the mass ratio of the metallic copper salt or copper oxide to the soluble cerium salt is 0.092:1.

[0034] Preferably, the calcination is carried out in an air atmosphere in a muffle furnace or a tube furnace, with a heating rate of 5° C. / min.

[0035] Calcination can decompose the active components and the precursors of the carrier into oxides, change the morphology and pore structure of the catalyst, and enhance the activity and sintering resistance of the catalyst.

[0036] Appropriate calcination time is beneficial to the interaction between catalyst component grains and the rearrangement of the crystal structure, thereby improving the crystallinity and lattice stability of the catalyst.

[0037] Furthermore, the calcination is carried out in an air atmosphere of a muffle furnace at a calcination temperature of 500° C. and a calcination time of 4 hours.

[0038] The present invention also provides application of the sintering-resistant copper oxide / cerium dioxide catalyst prepared by the preparation method in catalytic combustion of ethyl acetate.

[0039] Compared with the existing methods, the present invention has the following beneficial effects:

[0040] (1) The copper oxide / cerium dioxide catalyst prepared by the present invention forms a unique layered cerium dioxide nanosheet structure during the preparation process. The copper oxide particles are confined in the layered cerium dioxide nano-gap layer through the layered spatial confinement effect. In addition, the interaction between the layered cerium dioxide nanosheets and the copper oxide particles and the spatial spacing between the layered cerium dioxide nanosheets and the copper oxide particles limit the sintering phenomenon of the copper oxide particles and the layered cerium dioxide nanosheets that aggregate and grow at high temperatures. Compared with the catalyst prepared by the existing impregnation method, it has better activity and anti-sintering performance.

[0041] (2) Based on the impregnation method, the soluble cerium salt is directly impregnated into the metallic copper salt or copper oxide, and then dried, calcined and activated to obtain a highly active and sintering-resistant copper oxide / cerium dioxide catalyst. The operation is safe and simple, the cost is low, and it is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of this application, and do not constitute an improper limitation of the present invention.

[0043] Figure 1 Schematic diagram showing the effect of calcination temperature on the sintering-resistant copper oxide / cerium dioxide catalyst prepared by the present invention.

[0044] Figure 2 The catalytic activity diagram of ethyl acetate catalytic combustion of catalysts a-g obtained in Examples 1-5 of the present invention and Comparative Examples 1 and 2 is shown.

[0045] Figure 3 The X-ray diffraction patterns of catalysts a to g obtained in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2 are shown.

[0046] Figure 4 The scanning electron microscope spectra of catalysts a, b, f and g obtained in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2 are shown in FIG. Figure 4 (A) corresponds to catalyst a, Figure 4 (B) corresponds to catalyst b, Figure 4 (C) in the equation corresponds to catalyst f, Figure 4 (D) in the figure corresponds to catalyst g. Figure 5 The high-definition transmission electron microscopy images of catalysts a, b, f and g obtained in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2 are shown in FIG. Figure 5 (A) corresponds to catalyst a, Figure 5 (B) corresponds to catalyst b, Figure 5 (C) in the equation corresponds to catalyst f, Figure 5 (D) in the figure corresponds to catalyst g. DETAILED DESCRIPTION

[0047] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0048] Example 1

[0049] A copper oxide / cerium dioxide catalyst with a copper oxide mass percentage of 8.5% was prepared using cerium nitrate and copper acetate as precursors.

[0050] S1. Add 13.04 g of cerium nitrate hexahydrate to 10 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0051] S2. The impregnation solution obtained in step S1 is directly impregnated on 1.20 g of copper acetate and allowed to stand at room temperature for 24 hours to obtain a mixture;

[0052] S3. The mixture obtained in step S2 was placed in an oven at 100°C for 8 hours to obtain a precursor;

[0053] S4. The precursor obtained in step S3 is placed in a muffle furnace and heated to 500° C. at a rate of 5° C. / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst a having a copper oxide mass percentage of 8.5%.

[0054] The specific surface area of ​​catalyst a is 106.3 m 2 / g, the grain size of cerium dioxide is 9.4nm (see Table 1), and the average particle size of copper oxide is 3.2nm.

[0055] Example 2

[0056] A copper oxide / cerium dioxide catalyst with a copper oxide mass percentage of 8.5% was prepared using cerium nitrate and copper acetate as precursors.

[0057] S1. Add 13.04 g of cerium nitrate hexahydrate to 10 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0058] S2. The impregnation solution obtained in step S1 is directly impregnated on 1.20 g of copper acetate and allowed to stand at room temperature for 24 hours to obtain a mixture;

[0059] S3. The mixture obtained in step S2 was placed in an oven at 100°C for 8 hours to obtain a precursor;

[0060] S4. The precursor obtained in step S3 is placed in a muffle furnace and heated to 800°C at a rate of 5°C / min, and calcined for 4 hours to obtain a copper oxide / cerium oxide catalyst b having a copper oxide mass percentage of 8.5%, such as Figure 1 Schematic diagram showing the effect of calcination temperature on copper oxide / cerium dioxide catalyst

[0061] The specific surface area of ​​catalyst b is 37.7 m 2 / g, the grain size of cerium dioxide is 18.7nm (see Table 1), and the average particle size of copper oxide is 5.5nm.

[0062] Example 3

[0063] A copper oxide / cerium dioxide catalyst with a copper oxide mass percentage of 8.5% was prepared using cerium nitrate and copper carbonate as precursors.

[0064] S1. Add 13.75 g of cerium nitrate hexahydrate to 10 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0065] S2. The impregnation solution obtained in step S1 is directly impregnated on 1.40 g of copper carbonate and allowed to stand at room temperature for 24 hours to obtain a mixture;

[0066] S3. The mixture obtained in step S2 was placed in an oven at 100°C for 8 hours to obtain a precursor;

[0067] S4. The precursor obtained in step S3 is placed in a muffle furnace and heated to 500° C. at a rate of 5° C. / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst c having a copper oxide mass percentage of 8.5%.

[0068] The specific surface area of ​​catalyst c is 59.6 m 2 / g, the grain size of cerium dioxide is 13.1nm (see Table 1).

[0069] Example 4

[0070] A copper oxide / cerium dioxide catalyst with a copper oxide mass percentage of 8.5% was prepared using copper oxide obtained by calcining cerium nitrate and copper acetate as a precursor.

[0071] S1. Heat 1.25 g of copper acetate to 300°C in a muffle furnace at a rate of 5°C / min and calcine for 4 hours to obtain 0.5 g of copper oxide.

[0072] S2. Add 13.76 g of cerium nitrate hexahydrate to 10 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0073] S3. The impregnation solution obtained in step S2 is directly impregnated on 0.5 g of copper oxide obtained in step S1, and the mixture is allowed to stand at room temperature for 24 hours;

[0074] S4. The mixture obtained in step S2 was placed in an oven at 100 ° C for 8 hours to obtain a precursor;

[0075] S5. The precursor obtained in step S3 is placed in a muffle furnace and heated to 500° C. at a rate of 5° C. / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst d having a copper oxide mass percentage of 8.5%.

[0076] The specific surface area of ​​catalyst d is 62.2 m 2 / g, the grain size of cerium dioxide is 14.9nm (see Table 1).

[0077] Example 5

[0078] A copper oxide / cerium dioxide catalyst with a copper oxide mass percentage of 8.5% was prepared using copper oxide obtained by calcining cerium nitrate and copper nitrate as a precursor.

[0079] S1. Heat 1.51 g of copper acetate to 300°C in a muffle furnace at a heating rate of 5°C / min and calcine for 4 hours to obtain 0.5 g of copper oxide.

[0080] S2. Add 13.69 g of cerium nitrate hexahydrate to 10 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0081] S3. The impregnation solution obtained in step S2 is directly impregnated on 0.5 g of copper oxide obtained in step S1, and the mixture is allowed to stand at room temperature for 24 hours;

[0082] S4. The mixture obtained in step S3 was placed in an oven at 100°C for 8 hours to obtain a precursor;

[0083] S5. The precursor obtained in step S4 is placed in a muffle furnace and heated to 500° C. at a rate of 5° C. / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst e having a copper oxide mass percentage of 8.5%.

[0084] The specific surface area of ​​catalyst e is 63.6 m 2 / g, the grain size of cerium dioxide is 13.7nm (see Table 1).

[0085] Comparative Example 1

[0086] A copper oxide / cerium oxide catalyst with a copper oxide mass percentage of 8.5% was prepared using a cerium oxide carrier obtained by calcining copper nitrate and cerium nitrate.

[0087] S1. Add 2.83 g of copper nitrate trihydrate to 5.5 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0088] S2. 25.31 g of cerium nitrate was placed in an oven at 100 ° C for 4 hours, and then placed in a muffle furnace at a heating rate of 5 ° C / min to 300 ° C, and calcined for 4 hours to obtain 10 g of cerium dioxide;

[0089] S3. adding the cerium dioxide obtained in step S2 to the impregnation solution obtained in step S1, allowing all the impregnation solution to be completely adsorbed on the cerium oxide support, standing at room temperature for 24 hours to obtain a mixture, and baking the mixture in an oven at 100° C. for 8 hours to obtain a precursor;

[0090] S4. The precursor obtained in step S3 is placed in a muffle furnace and heated to 500° C. at a rate of 5° C. / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst f having a copper content of 8.5%.

[0091] The specific surface area of ​​catalyst f is 49.3 m 2 / g, the grain size of cerium dioxide is 23.4nm (see Table 1), and the average particle size of copper oxide is 7.9nm.

[0092] Comparative Example 2

[0093] A copper oxide / cerium oxide catalyst with a copper oxide mass percentage of 8.5% was prepared using a cerium oxide carrier obtained by calcining copper nitrate and cerium nitrate.

[0094] S1. Add 2.83 g of copper nitrate trihydrate to 5.5 mL of deionized water or distilled water and stir until completely dissolved to obtain an impregnation solution;

[0095] S2. 25.31 g of cerium nitrate was placed in an oven at 100 ° C for 4 hours, and then placed in a muffle furnace at a heating rate of 5 ° C / min to 300 ° C, and calcined for 4 hours to obtain 10 g of cerium dioxide;

[0096] S3. adding the cerium dioxide obtained in step S2 to the impregnation solution obtained in step S1, allowing all the impregnation solution to be completely adsorbed on the cerium oxide support, standing at room temperature for 24 hours to obtain a mixture, and baking the mixture in an oven at 100° C. for 8 hours to obtain a precursor;

[0097] S4. The precursor obtained in step S3 is placed in a muffle furnace and heated to 800°C at a rate of 5°C / min, and calcined for 4 hours to obtain a copper oxide / cerium dioxide catalyst g with a copper oxide mass percentage of 8.5%.

[0098] The specific surface area of ​​catalyst g is 4.5 m 2 / g, the grain size of cerium dioxide is 42.5nm (see Table 1), and the average particle size of copper oxide is 12.6nm.

[0099] Table 1: Specific surface area and cerium dioxide crystal size of catalysts a~g

[0100]

[0101] The cerium dioxide grain size is calculated by the Scherrer formula.

[0102] Test Example 1

[0103] The catalytic combustion activity of ethyl acetate was tested on each catalyst.

[0104] The catalyst activity test experiment was carried out by catalytic combustion of ethyl acetate (EA), a typical VOC compound, as a model compound in a fixed bed reactor (Vodo, China). In the experiment, 100 mg of catalyst was placed in a quartz reaction tube with an inner diameter of 6 mm, and the top and bottom of the catalyst were fixed with quartz wool. A thermocouple was inserted into the quartz wool above the catalyst, and the reaction temperature of the catalytic combustion was controlled by a temperature controller. During the catalytic combustion reaction, EA was maintained at 0°C with a cooler. The total flow rate of air containing 1000 ppm of EA was controlled to 100 ml / min by a mass flow controller, and the space velocity (GHSV) used in the reaction was 60,000 ml / h. The catalytic performance of the catalyst was analyzed online using a gas chromatograph (GC, Fuli) equipped with FID and SE-30 chromatographic columns.

[0105] Depend on Figure 2From the activity curve (the horizontal axis is temperature (Temperature), and the vertical axis is the conversion rate (EA Conversation) of ethyl acetate catalytic combustion as the reaction temperature increases), it can be seen that the copper oxide / cerium dioxide catalyst a prepared by the method of the present invention and calcined at 500°C has a higher catalytic activity than the copper oxide / cerium dioxide catalyst f prepared by the traditional impregnation method. In addition, after the copper oxide / cerium dioxide catalyst prepared by the method of the present invention is calcined at 800°C, the activity of catalyst b only slightly decreases. In contrast, after the copper oxide / cerium dioxide catalyst prepared by the traditional impregnation method is calcined under harsh conditions of 800°C, catalyst g is obviously sintered and deactivated. In addition, the method of the present invention is also applicable to copper oxide / cerium dioxide catalysts c, d and e prepared from copper carbonate and copper oxide, proving that a cerium-based transition metal catalyst with high catalytic activity and thermal stability can be prepared by the method of the present invention.

[0106] Test Example 2

[0107] XRD characterization was performed on each catalyst. Figure 3 shown.

[0108] Depend on Figure 2 The XRD spectra of catalysts a to g can be calculated by the Scherrer formula (as shown in Table 1). The cerium dioxide grain sizes of copper oxide / cerium dioxide catalysts a, b, f and g prepared with cerium nitrate as a precursor are 9.4nm, 18.7nm, 23.4nm and 42.5nm, respectively. The cerium dioxide grain sizes of copper oxide / cerium dioxide catalysts c, d and e prepared based on copper carbonate and different copper sources are c (13.1nm), d (14.9nm) and e (13.7nm), respectively. In addition, under high temperature calcination at 800°C, the cerium dioxide grain size of copper oxide / cerium dioxide catalyst b prepared by the method of the present invention increases from 9.4nm to 18.7nm. The cerium dioxide grain size of catalyst g prepared by the traditional method increases significantly from 23.4nm to 42.5nm. It is proved that the catalyst prepared by the method of the present invention has high thermal stability.

[0109] Test Example 3

[0110] Table 1 lists the specific surface areas of the prepared catalysts, which were calculated by the Brunner-Emmett-Teller (BET) method on a NOVA 2200e instrument using N2 adsorption at 77 K and a pressure range of 0.05-0.25P / P0. Before testing, all samples were degassed in vacuum at 300 °C for 3 h.

[0111] The specific surface areas of the copper oxide / cerium dioxide catalysts a, c, d, and e calcined at 500° C. provided by the method of the present invention are 106.3 m2 / g,59.6m 2 / g,62.2m 2 / g and 63.6m 2 / g. This is significantly higher than the specific surface area of ​​49.3 m2 of the copper oxide / cerium dioxide catalyst f calcined at 500 °C provided by the traditional method. 2 / g. The copper oxide / cerium dioxide catalyst prepared by the method of the present invention has a larger specific surface area than the catalyst prepared by the traditional method. After calcination at 800°C, the catalyst b prepared by the method of the present invention is reduced to 37.7m 2 / g; the specific surface area of ​​the catalyst prepared by the traditional method dropped sharply to 4.5m 2 / g, indicating that the method of the present invention can prepare sintering-resistant copper oxide / cerium dioxide catalyst.

[0112] Test Example 4

[0113] The catalysts were characterized by scanning electron microscopy (SEM). Figure 4 shown.

[0114] Depend on Figure 4 The SEM results show that catalyst a has an obvious layered structure of stacked cerium dioxide nanosheets with a diameter of about 580nm. Catalyst b calcined at a high temperature of 800°C is slightly sintered, the thickness of the cerium dioxide nanosheets increases, and the diameter of the nanosheets increases to about 830nm. This proves that the copper oxide / cerium dioxide catalyst prepared by the method of the present invention is only slightly sintered after high temperature treatment.

[0115] In contrast, after calcination at 800°C, obvious sintering and aggregation of copper oxide and ceria were observed for the g catalyst prepared by the conventional method. The copper oxide particles on the f and g catalysts prepared by the conventional method have weak interactions with the carrier, and the metal particles easily aggregate on the surface of the ceria carrier. In contrast, the a and b catalysts prepared by the method of the present invention have a unique nanosheet layered structure, and the copper oxide particles are evenly dispersed on the layered structure. During the sintering process, the stacked ceria nanosheets squeeze each other to form a smaller mesoporous space, which limits the migration and aggregation of Cu species in the catalyst. This may be the reason why the copper oxide / ceria catalyst prepared by the method of the present invention has high activity and high thermal stability.

[0116] Test Example 5

[0117] Each catalyst was characterized by high-definition transmission electron microscopy (HR-TEM). Figure 5 shown.

[0118] Depend on Figure 5The HR-TEM results show that the copper oxide particles of catalyst a are highly dispersed, and the average size of the copper oxide particles is 3.2 nm. In addition, in the copper oxide / cerium dioxide catalyst a, it is observed that the size distribution of the copper oxide particles is mainly concentrated at 3 nm, indicating that the copper oxide in the catalyst is uniformly dispersed on the support.

[0119] On the contrary, the particle size distribution range of the copper oxide particles on the f catalyst prepared by the conventional method is very wide, with an average particle size of 7.9 nm. It is proved that the copper oxide particles on the f catalyst are poorly dispersed and uneven in size. In addition, after high-temperature calcination of the g catalyst, the particle size of the copper oxide increases significantly, and the average particle size increases to 12.6 nm. The particle size of the copper oxide on the b catalyst prepared by the method of the present invention increases slightly, with an average particle size of 5.5 nm. The method of the present invention overcomes the shortcomings of poor dispersibility, low activity, poor thermal stability and easy sintering of metal particles in the conventional catalyst preparation method, so that the catalyst prepared by the present invention has higher catalytic activity and thermal stability.

[0120] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A sintering-resistant copper oxide / cerium dioxide catalyst, characterized in that: Ceria is used as a carrier, copper oxide is used as an active material, and copper oxide is confined in the nano-gap layer of ceria.

2. The copper oxide / cerium dioxide catalyst according to claim 1, characterized in that The cerium dioxide is a layered nanosheet structure, and the copper oxide is a particle structure.

3. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 1 or 2 comprises: S1. Adding a soluble cerium salt to a solvent and stirring until completely dissolved to obtain an impregnation solution; S2. impregnating the impregnation solution obtained in step S1 on a metallic copper salt or copper oxide, standing at room temperature to obtain a mixture, and drying the mixture to obtain a precursor; S3. The precursor obtained in step S2 is placed in an air atmosphere and calcined at a temperature of 400 to 800° C. for 2 to 8 hours to obtain a sintering-resistant copper oxide / cerium dioxide catalyst.

4. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The soluble cerium salt is one or more of cerium nitrate, cerium chloride, cerium citrate and cerium acetate.

5. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The solvent is one or more of water, methanol, ethanol and propanol.

6. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The mass ratio of the soluble cerium salt to the solvent is 1.30-1.40:

1.

7. The method for preparing the active copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The metal copper salt is one or more of copper acetate, copper carbonate and copper oxalate.

8. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The mass ratio of the metal copper salt or copper oxide to the soluble cerium salt is 0.03-0.1:

1.

9. The method for preparing the copper oxide / cerium dioxide catalyst according to claim 3, characterized in that: The calcination is carried out in an air atmosphere of a muffle furnace or a tube furnace, and the heating rate is 5°C / minute.

10. Use of the sintering-resistant copper oxide / cerium dioxide catalyst prepared by the preparation method according to any one of claims 3 to 9 in the catalytic combustion of ethyl acetate.

Citation Information

Patent Citations

  • Rod-like cerium dioxide loaded metal oxide nano-catalyst as well as preparation method and application thereof

    CN116493016A